Chemicals of concern in construction and demolition waste fine residues: A systematic literature review. (1st December 2021) - Molla, Adane Sewhunegn; Tang, Patrick; Sher, Willy; Bekele, Dawit Nega
Abstract: Despite the increasing use of chemical additives in construction and their potential threat to the environment and human health, many C&DW studies lack a comprehensive view of chemicals of concern (COC) in C&DW. This study systematically reviewed published studies from 2010 to August 2021 using a keyword search methodology to explore COC in C&DW fine residues based on 73 articles identified from 5 prominent databases. Results show that trace/heavy metals (As, Cr, Cu, Cd, and Pb) as well as high concentrations of toxic gasses (methane, hydrogen sulphide and mercury vapour) have been reported in landfills. Besides, organic chemicals such as polycyclic aromatic hydrocarbons, polychlorinated biphenyls, and brominated flame retardants have been found in landfill leachates in the Netherlands and widely detected in landfill leachates in Sweden, Japan, and Canada. The potential of these contaminants to cause health complications has also been reported. Carcinogenicity, liver and kidney damage, cumulative damage, neurological disorders and foetal damage were reported as associated health implications of exposure to COC from C&DW. A waste disposal lens was used to explore the factors that influence the environment and human health impacts (pH, gypsum and organic content, size fraction, atmospheric exposure and liquid infiltration rate). Despite environmental and health issues relating to C&DW fine residues, the ultimate destination for C&DW fine residues remains in general landfills. Although significant efforts in managing C&DW have been implemented at various levels, those specifically targeting C&DW fine residues remain sparse. Highlights: A systematic literature review has been conducted to explore adverse impacts (environmental and human health) from the reuse and disposal of C&DW fine residues. The ultimate destination for C&DW fine residues remains in general landfills. Fine fractions of C&DW are the worst when it comes to the release of contaminants and its composition. Heavy metals, flame retardants and high concentrations of toxic methane gases have been reported in landfills receiving C&DW fine residues. Further research into the safer disposal and management of C&DW fine residues is required to address the environmental issues of concern.